Changing visions in ESP development and teaching: Past, present, and future vistas - Dou, An Qi; Chan, Swee Heng; Win, Min Thein (Frontiers in Psychology, 2023)
Globalization and international development in language education have inspired a shift from the learning of traditional College English to English for Specific Purposes (ESP). This article begins with a section on the methodology used to develop the literature review. From various literatures, a historical perspective was first presented for the period, 1962 to the present day, and accompanied by a review on the teaching approaches. The purpose was to reveal emerging trends in ESP development and forefront the strength of association between ESP development and the changes in teaching approaches. Then it focuses on the relationship between needs analysis and ESP, as needs analysis is well recognized as a vital ESP characteristic and it is given a comprehensive revisit as an update in ESP development. The review continues with some insights into recent studies from various countries to reflect on various aspectual developments of current ESP practices that illustrate the dynamics of growing research agendas that have implications for current and future ESP research directions. Finally, future vistas for ESP development and teaching are affirmed. The paper concludes on the note on the importance of knowing past and future ESP developments, and the prioritizing of effective teaching based on soundly designed materials tailored to particular student-centered needs and wants.